2022
DOI: 10.3390/s22134750
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Generalization of Supervised Fabric Anomaly Detection Methods to Unseen Fabrics

Abstract: Fabric ad tries to detect anomalies (i.e., defects) in fabrics, and fabric ad approaches are continuously improved with respect to their ad performance. However, developed solutions are known to generalize poorly to previously unseen fabrics, posing a crucial limitation to their applicability. Moreover, current research focuses on adapting converged models to previously unseen fabrics in a post hoc manner, rather than training models that generalize better in the first place. In our work, we explore this poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The model was trained with the TILDA dataset and compared to mainstream deep learning models. Rippel et al [ 36 ] assessed different models for fabric anomaly detection. The results showed that the techniques used in the method improve the model resistance as well as the generalization of the supervised learning technique.…”
Section: Introductionmentioning
confidence: 99%
“…The model was trained with the TILDA dataset and compared to mainstream deep learning models. Rippel et al [ 36 ] assessed different models for fabric anomaly detection. The results showed that the techniques used in the method improve the model resistance as well as the generalization of the supervised learning technique.…”
Section: Introductionmentioning
confidence: 99%